Indonesian Newsroom Management on Uyghur News Coverage - Prastya, Narayana Mahendra; Pambudi, Fikri S.; Ningsih, Ida Nuraini Dewi Kodrat (CHANNEL: Jurnal Komunikasi, 2022)
The case of the Uyghur ethnic in Xinjiang, China, has drawn global attention, and so has the media coverage of this issue. In Indonesia, the Uyghur issue attracts people’s attention due to religious sentiment. This article aims to determine how Indonesian mass media newsroom management is in Uyghur news coverage. Much previous research discusses how Indonesian media news coverage towards the Uyghur issue, but most use content analysis methods. Meanwhile, the primary data of this article is an interview with the journalist. Two media, Tempo and Republika, have been chosen as the subject matter, as both have different ideologies: human rights (Tempo) and Islam (Republika). The results show that both media use psychological proximity as a consideration in choosing information and news angles for the Uyghur issue. In organizing, both media do not form specific teams or order journalists based on particular skills to cover it. In the fundamental phase, both media admit difficulties in news coverage due to the limited access in Xinjiang directly, so for the news that happens in China. They can only use foreign news agencies, then rewrite the information to contextual the issue for Indonesian readers. For issues related to Uyghur in Indonesia, both media gather the information by direct reporting and interviewing Indonesian government officials or Islamic organizations. For the controlling phase, Republika did formal and informal procedures. Meanwhile, Tempo uses feedback from readers mentioned on social media and a board called Ombudsman.